THE NEED ANALYSIS FOR PBL-BASED E-BOOK LEARNING WITH AR TO ENHANCE DIGITAL LITERACY AND PROBLEM SOLVING SKILLS OF ELEMENTARY SCHOOL - Dewi, Santi Kurnia; Kuswandi, Dedi; Pristiani, Riska; Kusumaningrum, Shirly Rizki; Mardhatillah, Mardhatillah (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
Education in Indonesia faces the challenge of enhancing digital literacy and student’s problem-solving abilities. In the context, the development of more interactive technology-based learning materials presents an effective solution. This study aims to analyze the need for developing Problem-Based Learning (PBL) e-book supported by Augemented Reality (AR) media to improve digital literacy and problem-solving skills in the learning of science and social studies (IPAS) at the elementary school phase C level. The result of the analysis indicate that IPAS learning still faces challenges in understanding abstract material and lacks engaging media. Therefore, the development of PBL based e-book with AR media is considered highly relevant and necessary to address the challenges of 21st century learning.